The social educator in Spanish schools: an analysis of school regulations - Juan Agustín González Rodríguez (University of Bologna, 2022)
Spain is one of the European countries that has changed the most in recent years. The arrival of population of foreign origin has been one of the major changes and its impact is particularly evident in the educational system. Many tools have been introduced in an attempt to manage diversity and coexistence, including the introduction of the social educator in schools. However, its introduction has not been homogeneous: in some communities there have been educators in schools for 20 years, while other communities do not have them yet. This article seeks to delineate the recognized profile of social educators in their regulations and functions in schools. Methodologically, the work was carried out through a comparison of regional regulations that recognize the social educator as a professional in the school context. The results show that there are few communities that have included social education professionals at school and that, among those who have done so, most focus on coexistence and few on interculturality.